1995
DOI: 10.1074/jbc.270.26.15658
|View full text |Cite
|
Sign up to set email alerts
|

The SH2 Domains of Src Family Kinases Associate with Syk

Abstract: Src family kinases (Lyn, Fyn, Lck, and Blk) and Syk, a tandem SH2 domain containing tyrosine kinase, have been demonstrated to be associated with the antigen receptor in B cells. Both of these categories of tyrosine kinases are presumed to be critical players in the process of antigen-mediated signal transduction. Cross-linking of membrane immunoglobulin on the surface of B cells leads to the activation of Lyn, Fyn, and Blk, which presumably associate with the cytoplasmic tails of the membrane immunoglobulin-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…5), suggesting a possible suppressive role of Src kinase(s) in Syk activation (49). It was also reported that Src family kinases (Lyn and Btk) co-immunoprecipitate with Syk in activated B cells (50,51). It is thus likely that the agarosebound Syk used in our current study also carries these kinases.…”
Section: Discussionmentioning
confidence: 80%
“…5), suggesting a possible suppressive role of Src kinase(s) in Syk activation (49). It was also reported that Src family kinases (Lyn and Btk) co-immunoprecipitate with Syk in activated B cells (50,51). It is thus likely that the agarosebound Syk used in our current study also carries these kinases.…”
Section: Discussionmentioning
confidence: 80%
“…Since the phosphorylation of these sites in Syk is also required for the activation of Lck, by its phosphorylation at Y192 within its SH2 domain, it is possible that Syk is also involved in the positive regulation of Srcfamily kinases (Couture et al, 1994b). This further suggests that the observed association between Lck and Syk in stimulated cells (Couture et al, 1994b) and the binding of SH2 domains of various members of the Src-family of kinases to tyrosyl phosphorylated Syk in vitro (Aoki et al, 1995;Couture et al, 1994a) is mediated by Syk's phosphorylation at Y518/519. The corresponding tyrosyl residues within the activation loop of ZAP-70 ± Y492 and Y493 have also been shown to undergo phosphorylation following TCR aggregation, and to be essential for the signaling function of ZAP-70 Wange et al, 1995).…”
Section: Syk and Zap-70 Recruitment And Activationmentioning
confidence: 75%
“…BLK is a member of the Src kinase family involved in B-cell receptor signaling, 188 and might be important for the development of the B-cell repertoire. Two recent GWASs revealed BLK to be a novel risk locus for SLE.…”
Section: 187mentioning
confidence: 99%